Pengaruh Substitusi Pakan Komersial dengan Pakan Hasil Samping Agroindustri pada Babi Fase Grower: Effect of Agroindustrial By-Product as Commercial Feed Substitution on Grower Phase Pigs - Matutu, Ardi; Wiryawan, I Komang Gede; Salundik; Negara, Windu (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This research was conducted to determine the impact of substituting commercial feed with agroindustrial by-product feed on the growth performance of pigs in the grower phase and the benefits obtained by farmers. A total of 20 pigs aged 18 weeks were tested in a randomized block design with four treatments and five replications. The feed treatments were P0= commercial feed (CP 552), P1= 50% CP552 and 50% agroindustry feed, P2= 100% agroindustry feed, and P3= P2 feed with the addition of phytase and mannase enzymes. The results showed that feed consumption, body weight gain, and feed conversion were not significantly different among the treatments. The digestibility of the P0 was significantly higher than that of P1, P2, and P3 (p<0.05). The digestibility of the P3 was not significantly different from that of the P1; however, it was significantly higher than P2 (p<0.05). The IOFC of P2 was higher than P0 and P1, while P3 resulted in the highest IOFC among treatments. It can be concluded that utilizing feed containing agro-industrial by-products could substitute 100% of commercial feed in growing pigs and provides 60% higher income than commercial feed. Moreover, additional phytase and mannase enzymes on agroindustrial by-products feed might provide 89% higher income than commercial feed. Key words: agroindustry, by-products, commercial feed, pigs, substitution